Influence of somatic cell count in heifers on lifetime milk yield and disease management - Archer, Simon C. (2013)
The aim was to assess the impact of milk somatic cell count (SCC) during the first lactation on the lifetime milk production of cows, and therefore estimate potential savings through heifer mastitis control. Cow level SCC over the first lactation was summarised as SCC between 5 and 30 days in milk (SCC1), and the geometric mean and variance of first lactation SCC. The impact of SCC1 on cumulative milk yield over different time periods was assessed for cows in Irish, English, and Welsh dairy herds. The impact of SCC1 and the geometric mean and variance of first lactation SCC on lifetime milk yield, and the association between SCC1 and disposal risk were assessed for cows in Irish dairy herds. Increase in SCC throughout the first lactation was associated with large reductions in the milk yield of cows, and increased disposal risk. Bayesian micro-simulation was used to demonstrate the impact in different herd scenarios. This was extended to synthesise evidence on potential savings using previous research, to estimate the economic impact of specific interventions to reduce the prevalence of cows with high SCC1. There was considerable variation between herds in the apparent impact of SCC1 on SCC throughout the first lactation, indicating the importance of a herd specific approach to control. ‘Cost effectiveness’ of interventions to reduce the prevalence of cows with high SCC1, was found to be highly dependent on the willingness of decision makers to pay for control measures. Increase in herd size was associated with increase in cow SCC, highlighting a need for improved management of mastitis when expansion is planned. An important component of this should be through monitoring and control of mastitis in heifers, especially those in spring-calving Irish dairy herds.